2010
DOI: 10.1007/s12289-010-0798-9
|View full text |Cite
|
Sign up to set email alerts
|

Tool flank wear analyses on AISI 440 C martensitic stainless steel by turning

Abstract: Hard turning of materials is a process where dimensional accuracies, dimensional controls and surface roughness are easily obtained. Currently hard components are produced by hard machining in a very short time which also saves on cost. Martensitic stainless steel is difficult to cut due to the presence of high amount of chromium and makes the material harder. AISI 440 C hardness is maintained through induction hardening process. The cutting tool used for this material is normally a super hard cutting tool lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Authors have noted that cutting speed is the main parameter which affect flank wear and as cutting speed increases to 175 m/min, the flank wear decreases. Hasan and Thamizhmanii (2010) analyzed tool wear during turning of AISI 440C martensitic stainless steel using CBN cutting tool. They found that flank and crater wears were caused by severe abrasion phenomenon and also by high generation of heat during machining especially at low cutting speed, and low feed rate.…”
Section: Introductionmentioning
confidence: 99%
“…Authors have noted that cutting speed is the main parameter which affect flank wear and as cutting speed increases to 175 m/min, the flank wear decreases. Hasan and Thamizhmanii (2010) analyzed tool wear during turning of AISI 440C martensitic stainless steel using CBN cutting tool. They found that flank and crater wears were caused by severe abrasion phenomenon and also by high generation of heat during machining especially at low cutting speed, and low feed rate.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos investigadores afirman que el desgaste del flanco es el factor más importante para evaluar el desgaste de la herramienta de corte [9][10].…”
Section: Introductionunclassified
“…During turning one of the important factors is tool wear whether it is soft or hard machining. Flank wear is the most important wear which will affect the smoothness of the product, cost of operation and performance [5]. Tool wear mechanisms are generally influenced by four phenomenons namely: abrasion, thermal softening, diffusion and notching at depth of cut and trailing edge [6].…”
Section: Introductionmentioning
confidence: 99%